Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada LPD Di Kecamatan Denpasar Utara - perbarini, Ni Kadek ayu; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 1 No 1 (2012), 2012)
The information system is very important in the success of an organization, such as organizational Lembaga Perkreditan Desa. Lembaga Perkreditan Desa in Denpasar Utara District has implemented Accounting Information Systems - computer based. This study used multiple linear regression analysis techniques, classical assumption test and equipped with testing instruments. The results of the analysis concluded that the User Involvement, Top Management Support, Education and Training has a significant influence on the performance of Accounting Information System are proxied on Accounting Information System User and Usage Satisfaction. Personal Capability Engineering has a positive but not significant effect on the performance of Accounting Information System are proxied by the Accounting Information System User and Usage  Satisfaction. Formalization Development of a significant effect on the performance of Accounting Information System proxied on User Satisfaction, and no significant positive effect on the performance of Accounting Information System are proxied to the use of Accounting Information System.
Keywords: System User Satisfaction, System Usage